Exposure to Inorganic Arsenic Is Associated with Increased Mitochondrial DNA Copy Number and Longer Telomere Length in Peripheral Blood - Ameer, Syeda S.; Xu, YiYi; Engström, Karin; Li, Huiqi; Tallving, Pia; Nermell, Barbro; Boemo, Analia; Parada, Luis A.; Peñaloza, Lidia G.; Concha, Gabriela; Harari, Florencia; Vahter, Marie; et al. (Frontiers in Cell and Developmental Biology, 2016)
Background: Exposure to inorganic arsenic (iAs) through drinking water causes cancer. Alterations in mitochondrial DNA copy number (mtDNAcn) and telomere length in blood have been associated with cancer risk. We elucidated if arsenic exposure alters mtDNAcn and telomere length in individuals with different arsenic metabolizing capacity. Methods: We studied two groups in the Salta province, Argentina, one in the Puna area of the Andes (N = 264, 89% females) and one in Chaco (N = 169, 75% females). We assessed arsenic exposure as the sum of arsenic metabolites [iAs, methylarsonic acid (MMA), dimethylarsinic acid (DMA)] in urine (U-As) using high-performance liquid chromatography coupled with hydride generation and inductively coupled plasma mass spectrometry. Efficiency of arsenic metabolism was expressed as percentage of urinary metabolites. MtDNAcn and telomere length were determined in blood by real-time PCR. Results: Median U-As was 196 (5–95 percentile: 21–537) μg/L in Andes and 80 (5–95 percentile: 15–1637) μg/L in Chaco. The latter study group had less-efficient metabolism, with higher %iAs and %MMA in urine compared with the Andean group. U-As was significantly associated with increased mtDNAcn (log2 transformed to improve linearity) in Chaco (β = 0.027 per 100 μg/L, p = 0.0085; adjusted for age and sex), but not in Andes (β = 0.025, p = 0.24). U-As was also associated with longer telomere length in Chaco (β = 0.016, p = 0.0066) and Andes (β = 0.0075, p = 0.029). In both populations, individuals with above median %iAs showed significantly higher mtDNAcn and telomere length compared with individuals with below median %iAs. Conclusions: Arsenic was associated with increased mtDNAcn and telomere length, particularly in individuals with less-efficient arsenic metabolism, a group who may have increased risk for arsenic-related cancer.